2021
DOI: 10.3390/cancers13081909
|View full text |Cite
|
Sign up to set email alerts
|

Loss of RET Promotes Mesenchymal Identity in Neuroblastoma Cells

Abstract: Aberrant activation of anaplastic lymphoma kinase (ALK) drives neuroblastoma (NB). Previous work identified the RET receptor tyrosine kinase (RTK) as a downstream target of ALK activity in NB models. We show here that ALK activation in response to ALKAL2 ligand results in the rapid phosphorylation of RET in NB cells, providing additional insight into the contribution of RET to the ALK-driven gene signature in NB. To further address the role of RET in NB, RET knockout (KO) SK-N-AS cells were generated by CRISPR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 68 publications
1
12
0
Order By: Relevance
“…Importantly, DDR2 was one of the mesenchymal signature genes, while RET and ALK were listed in the adrenergic set. In line with this, Siaw et al recently showed that loss of RET promotes mesenchymal identity in neuroblastoma cells [56]. Moreover, the authors also observed that RET expression and activity are directly regulated by ALK.…”
Section: Ddr2mentioning
confidence: 65%
See 1 more Smart Citation
“…Importantly, DDR2 was one of the mesenchymal signature genes, while RET and ALK were listed in the adrenergic set. In line with this, Siaw et al recently showed that loss of RET promotes mesenchymal identity in neuroblastoma cells [56]. Moreover, the authors also observed that RET expression and activity are directly regulated by ALK.…”
Section: Ddr2mentioning
confidence: 65%
“…Initially, Iwamoto et al [50] reported neuroblastoma development in a transgenic mouse that carried the RET oncogene driven by a mouse metallothionein regulatory element. Additional reports using cell lines support a role for GDNF/RET signaling in differentiation, migration, and metastasis [51][52][53][54][55][56]. Recently, using neuroblastoma models carrying activating Alk mutations in the context of MYCN overexpression, Cazes et al [57] demonstrated that RET is upregulated in an ALK-dependent fashion.…”
Section: Retmentioning
confidence: 97%
“…( E ) Bar plot showing RNA-Seq-based log2FC values (mean ± 95% CI) of 276 genes involved in the DDR for different NB cell lines and drug treatments as indicated. Data were derived from five previously published studies ( 14 , 19 , 20 , 24 , 25 ) with DDR genes as defined by Knijnenburg et al ( 23 ). CLB-BAR, CLB-GE, and NB1 are ALK-dependent lines.…”
Section: Resultsmentioning
confidence: 99%
“…E. Bar plot showing RNA-Seq based log2FC values (mean ± 95% confidence interval) of 276 genes involved in the DNA Damage Response (DDR) for different NB cell lines and drug treatments as indicated. Data derived from 5 previously published studies 15,19,20,83,84 with DDR genes as defined by Knijnenburg et al 23 . F. ALK-positive CLB-BAR, CLB-GE, and CLB-GAR NB cells were treated with lorlatinib (30 nM) or etoposide (500 nM), either alone or in combination for 24 h. DNA damage was monitored by immunoblotting of p-H2A.X (S139).…”
Section: Resultsmentioning
confidence: 99%
“…The mass spectrometry proteomics data have been deposited to the ProteomeXchange Consortium 81 via the PRIDE 82 studies 15,19,20,83,84 with DDR genes as defined by Knijnenburg et al 23 Hierarchical clustering performed using the Ward.2 method with dendrograms indicated. Genes active in ATR, ATM, DNAPK and mTOR pathways indicated on the left.…”
Section: Cell Differentiation Assaysmentioning
confidence: 99%